Synthesis, Anti-Inflammatory and Anti- Nociceptive Activities and Cytotoxic Effect of Novel Thiazolidin-4-ones Derivatives as Selective Cyclooxygenase (COX-2) Inhibitors - Seyed Adel Moallem; Mohsen Imenshahidi; Narges Shahini; Ahmad Reza Javan; Mohsen Karimi; Mona Alibolandi; Morteza Ghandadi; Leila Etemad; Vahidehsadat Motamedshariaty; Toktam Hosseini; Farzin Hadizadeh (Iranian Journal of Basic Medical Sciences, 2013)
Objective(s): Nowadays, COX- 2 inhibitors such as valdecoxib are removed from the market because of their cardiovascular toxicity and their potential to increase the risk of strokes. In response to this, medicinal chemists have attempted to synthesize new classes of COX-2 Inhibitors.